(untitled) (Medical Forum Monthly, 2024)
Objective: Importance of accurate defect size estimation and its relevance in open inguinal hernia repair. Study Design: Descriptive prospective cohort study Place and Duration of Study: This study was conducted at the Department of Surgery Abbasi Shaheed Hospital with one year duration February 2023 to February 2024. Methods: 194 participants selected through consecutive sampling divided into two groups F1 and F2. 97 participants in each group. Ethical review board approved study. For defect size estimation European hernia society (EHS) classification is used in F1 and ultrasound and EHS classification in F2.Lichtenstein repair with mesh size 6x11cm opted. Overlapping of mesh, defect sizes, fixation of mesh, recurrence, seroma, wound dehiscence, transient testicular swelling, testicular atrophy& urinary retention are taken as variables analyzed through mean, median mode, relative risk, P-value, graph and charts. Statistical Package for social sciences (SPSS) used. Patients followed up on 10th day3rd month and 6th month postoperatively. Results: Mean age in F1 and F2 44years,median 45 years and mode 50 years, standard deviation 15.868 .In F1 defect sizes measured through EHS classification: no patients <1.5cm(01 finger breadth),49.48% patients 1.5-3 cm(02 finger breadth),50.5% patients >3cm(>2 finger breadth). In F2 group: 3% patients <1.5cm(01 finger breadth), 59.7% patients 1.5-3cm (2 finger breadth),37.11% patients >3cm (>2finger breadth). In Group F1: recurrence 2%,seroma 13%,wound dehiscence 11%,transient testicular swelling 3%, spinal headache 10%,testicular atrophy 1% and 3% patients had urinary retention. In Group F2: recurrence 1%, seroma 4%, wound dehiscence 3%, transient testicular swelling 1%, spinal headache 5% , no testicular atrophy , and urinary retention found in 1% patients. Conclusion: Accurate defect size estimation has significant impact on outcome in open inguinal hernia repair furthermore, proper mesh implantation reduce postoperative complications.